2016
DOI: 10.1136/thoraxjnl-2015-207045
|View full text |Cite
|
Sign up to set email alerts
|

Randomised crossover trial of telemonitoring in chronic respiratory patients (TeleCRAFT trial)

Abstract: ObjectiveTo assess the impact of home telemonitoring on health service use and quality of life in patients with severe chronic lung disease.DesignRandomised crossover trial with 6 months of standard best practice clinical care (control group) and 6 months with the addition of telemonitoring.Participants68 patients with chronic lung disease (38 with COPD; 30 with chronic respiratory failure due to other causes), who had a hospital admission for an exacerbation within 6 months of randomisation and either used lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
106
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(112 citation statements)
references
References 23 publications
2
106
0
4
Order By: Relevance
“…Although a few studies have suggested that combining symptoms and physiological variables, such as pulse and oxygen saturation, can identify COPD exacerbations 34 , subsequent randomised trials have not shown any effect of monitoring on TTFH and/or patient's quality of life, similar to our findings [11][12][13]15,16 . However, while other trials recruited previously hospitalised patients, we studied COPD patients reporting two or more exacerbations in the previous year, i.e.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Although a few studies have suggested that combining symptoms and physiological variables, such as pulse and oxygen saturation, can identify COPD exacerbations 34 , subsequent randomised trials have not shown any effect of monitoring on TTFH and/or patient's quality of life, similar to our findings [11][12][13]15,16 . However, while other trials recruited previously hospitalised patients, we studied COPD patients reporting two or more exacerbations in the previous year, i.e.…”
Section: Discussionsupporting
confidence: 80%
“…As there was no difference between study arms we can hypothesise that the attritions were mostly due to the multiple contacts for collecting questionnaires and the feeling of limitation in freedom to act induced by participating in a clinical trial rather than specific issues related to the monitoring procedures. The number of respiratory alerts per patients was roughly one every two months, a small number compared to other similar telemonitoring trials in which alerts were based on symptoms and/or other variables 11,12,41 . Compared to those studies, the monitoring system based on continuous self-evaluation of lung function by FOT led to neither a major increase in time burden for healthcare personnel nor an increase in drug prescriptions when compared to standard practice, allowing it to be incorporated into a clinical service.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The median CAT at study inclusion was 17 points (range 1-30, interquartile range [IQR] [13][14][15][16][17][18][19][20][21][22]. The compliance to fill out the weekly CAT was 91% (2,364 of 2,538 required entries) in our study population.…”
Section: Resultsmentioning
confidence: 99%
“…There are only few randomized controlled trials (RCTs) investigating THC for COPD and even less investigating HRQoL. [16][17][18][19][20][21][22][23] A study from the UK over 12 months found 20 It is important to mention that the THC interventions differed considerably between these studies. The "reaction interval" varied daily, weekly, every 2 weeks and monthly.…”
mentioning
confidence: 99%